PENGARUH KELIMPAHAN PLANKTON DAN KUALITAS AIR TERHADAP PERFORMA PERTUMBUHAN UDANG VANNAME PADA SISTEM BUDIDAYA INTENSIF - Aisyah, Diana; Ramadhani, Ayu Winna; Fattah, Mochammad; Sofiati, Dwi; Anandya, Asyifa (JURNAL LEMURU, 2023)
In intensive shrimp farming systems, apart from feed, the presence of plankton is an important factor in shrimp farming as a tropic level in waters where the main producers in the waters are phytoplankton. The nature of plankton in the waters is not only beneficial but also detrimental. The condition of a waters will also affect the pattern of distribution or distribution of plankton both horizontally and vertically, so that it will affect the abundance of plankton which in turn will affect the value of primary productivity. This study aims to determine the ratio of plankton abundance and water conditions to the growth performance of vaname shrimp (Litopenaeus vannamei) organisms. The method used in this research is descriptive using the sampling method. The analysis was carried out in the form of abundance of plankton species and water physico-chemical parameters (temperature, pH, salinity, DO, ammonia, nitrate and nitrite). The results obtained found 5 classes of plankton (chlorophyta, cyanophyta, diatoms, dinoflagellate, zooplankton) with varying abundances where the highest abundance was found in classes and cyanophyta. Water quality is still within normal limits for vannamei shrimp growth.